Current Trends of Targeted Drug Delivery for Oral Cancer Therapy - Zhang, Mingming; Liang, Jianqin; Yang, Yanyu; Liang, Huize; Jia, Huaping; Li, Dawei (Frontiers in Bioengineering and Biotechnology, 2020)
Oral cancer is an aggressive tumor that invades the local tissue and can cause metastasis and high mortality. Conventional treatment strategies, e.g. surgery, chemotherapy and radiation therapy alone or in combinations, possess innegligible issues and significant side and adverse effects for the clinical applications. Currently, targeting drug delivery is emerging as an effective approach for oral delivery of different therapeutics. Herein we provide a state-of-the-art review on the current progress of targeting drug delivery for oral cancer therapy. Variously oral delivery systems including polymeric/inorganic nanoparticles, liposomes, cyclodextrins, nanolipids and hydrogels-based forms are emphasized and discussed, and biomimetic systems with respect to oral delivery like therapeutic vitamin, exosomes, proteins and virus-like particles are also described with emphasis on the cancer treatment. A future perspective is also provided to highlight the existing challenges and possible resolution toward clinical translation of current oral cancer therapies.